2014
DOI: 10.1016/j.neuroscience.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of tyrosine hydroxylase in tree shrew nucleus accumbens core and shell

Abstract: Many behavioral, physiological, and anatomical studies utilize animal models to investigate human striatal pathologies. Although commonly used, rodent striatum may not present the optimal animal model for certain studies due to a lesser morphological complexity than that of non-human primates, which are increasingly restricted in research. As an alternative, the tree shrew could provide a beneficial animal model for studies of the striatum. The gross morphology of the tree shrew striatum resembles that of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 79 publications
0
20
1
Order By: Relevance
“…10 Regions from the core and shell were blocked using the calbindin-stained sections as a guide. For each region, 3 blocks per case, at least 240 μm apart rostrocaudally, were used to obtain semithin sections.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…10 Regions from the core and shell were blocked using the calbindin-stained sections as a guide. For each region, 3 blocks per case, at least 240 μm apart rostrocaudally, were used to obtain semithin sections.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Serial ultrathin sections (90 nm thickness) from each block were mounted on Formvar-coated copper grids, and photographed at 80 kV on a Hitachi transmission electron microscope, as detailed previously. 10 …”
Section: Nucleus Accumbens Ultrastructure In Schizophreniamentioning
confidence: 99%
“…In addition to these common solutions, the shell was further subdivided into medial and lateral areas, or even more subregions, based on their unique sets of inputs and outputs [Ikemoto, 2007]. The rostral pole was identified because of its specific efferent projections in rodents [Zahm and Brog, 1992;Zahm and Heimer, 1993] but not in primates [Ikemoto et al, 1995;McCollum and Roberts, 2014]. Although multiple levels of complex organization have been identified, to date the shell-core dichotomy has been the most intensely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Species‐dependent differentiation provides some insights into the evolution and adaptation of cerebellar lobules in various mammals (Luo et al, ).According to recent studies, the tree shrew is the closest living relative of primates (Fan et al, ; Kriegs, Churakov, Jurka, Brosius, & Schmitz, ; Yao, ). Other nongenomic evidences of morphological and anatomical characteristics in the tree shrew brain also support the relationship of tree shrews to primates (McCollum & Roberts, ; Ni et al, ; Ni et al, ; Rice, Roberts, Melendez‐Ferro, & Perez‐Costas, ; Romer et al, ). Previous studies have indicated that the tree shrews is widely used to study the visual system (Baldwin, Balaram, & Kaas, ; Petry & Bickford, ), motor system (Baldwin, Cooke, & Krubitzer, ), social stress (Fuchs & Flugge, ; Wang et al, ) and other neural systems.…”
Section: Introductionmentioning
confidence: 73%